P-87 The importance of educating healthcare workers (HWC) on advance care planning (ACP) in a south-east asian (SEA) acute hospital setting: The national heart centre singapore (NHCS) experience. (1st September 2015) - Lim, SM; Tan, SH; Ng, CSH; Lau, Cindy SL; Wong, Jane CQ; Tan, BC; Wong, G; Sim, KLD
Abstract : Background: NHCS Heart Failure team and Medical Social Workers (MSW) spearheaded the implementation of ACP in August 2012. The programme now incorporates a component of intra-institution education of HCWs, specifically with cardiac nurses and physicians. Aim: To provide on-going education and address misconceptions of ACP amongst HCWs in a SEA acute hospital setting, in view that discussion of patients' crucial end-of-life treatment preferences is an avoided topic amongst HCWs in their daily frontline patient interactions and care. Methods: NHCS ACP model was enhanced to include sub-clinical teams for education. Education on ACP was disseminated via interactive lecture-style presentations by the MSW team, with the support from key NHCS Senior Management. Results: 122 registered and enrolled nurses attended 3 one-hour lectures. About 40 Cardiologists and medical officers attended a 30-minute lecture. Discussion: Frontline HCWs tend to perceive ACP as a sensitive topic and are uncomfortable bringing it up in their patient care, despite perceiving ACP as an essential discussion framework to minimise conflict or dilemma during medical emergencies. Conclusion: To garner support from essential healthcare stakeholders and help them appreciate ACP as part of standard patient care, ongoing education for HCWs is necessary to overcome the cultural barriers and to shift perceptions on ACP. Further development of a skills-based education programme may be necessary to equip HCW with the soft skills of introducing ACP as standard patient care in NHCS.